The credos of eight Black leaders converting obstacles into opportunities - Asnbro, John J. (Lanham University Press of America, 2004)
Based on a detailed analysis of 21,000 pages of primary works including numerous biographies, this book presents that author's formulations of the objectives, strategies, and tactics of eight African-American and African activists_Frederick Douglass, Booker T. Washington, Marcus Garvey, W.E.B. Du Bois, Malcolm X, Martin Luther King, Nelson Mandela, and Archbishop Desmond Tutu.
Includes bibliographical references (p. [231]-234)
Keywords: African American political activists -Biography.